Sustainable Tourism Development Strategy for Bakaran Wetan Village, Pati Regency Based on Edutourism: Community Based Tourism (CBT) Approach - Setyaputri, Nanda Aji; Rusdarti; Rachmadi, Moch Faizal (International Journal of Green Tourism Research and Applications, 2025)
Bakaran Wetan Village, Central Java Province is one of the areas in Indonesia with various superior tourism potentials such as the Bakaran Sudewi Batik Museum, Punden Nyai Ageng and Ki Dalang Soponyono and others that are closely related to historical, social, cultural philosophies and educational elements. However, the main problem faced is the lack of involvement of stakeholders, especially the community, in an integrated, integrated and active manner in realizing it as a sustainable tourism village. Based on this, the objectives of this study are: 1) To identify the potentials and problems in developing sustainable tourism in Bakaran Wetan Village and 2) To identify actors/stakeholders who play a major role in realizing it as a sustainable tourism village based on edutourism. This research method is mixed methods with a qualitative descriptive and quantitative approach based on actor/stakeholder mapping using the Matrix of Alliance and Conflict: Tactics, Objectives and Recommendation (MACTOR). The results of the study show that the Youth, Sports and Tourism (DINPORAPAR) has the highest convergence value with the Office of Tourism Awareness Group (POKDARWIS), which integrates it with the roles of other stakeholders, namely the Education and Culture Office (DISDIKBUD), Museum Management (MUSEUM) and the Office of Regional Development Planning, Research and Innovation (BAPPERIDA). Meanwhile, related to the identification of actor objectives, the highest convergence is the optimization of edutourism tour packages (EDUTOURISM) with synergy efforts to develop the tourism sector based on stakeholder intensification (SINERGITAS). The practical impact of this research is to map the synergy between stakeholders involved in the development of sustainable tourism while also determining the priority strategies to be implemented in Bakaran Wetan Village.